Chronic Reduction of GIP Secretion Alleviates Obesity and Insulin Resistance Under High-Fat Diet Conditions - Nasteska, Daniela; Harada, Norio; Suzuki, Kazuyo; Yamane, Shunsuke; Hamasaki, Akihiro; Joo, Erina; Iwasaki, Kanako; Shibue, Kimitaka; Harada, Takanari; Inagaki, Nobuya (Diabetes (New York, N.Y.), 2014)
Gastric inhibitory polypeptide (GIP) exhibits potent insulinotropic effects on β-cells and anabolic effects on bone formation and fat accumulation. We explored the impact of reduced GIP levels in vivo on glucose homeostasis, bone formation, and fat accumulation in a novel GIP-GFP knock-in (KI) mouse. We generated GIP-GFP KI mice with a truncated prepro-GIP gene. The phenotype was assessed in heterozygous and homozygous states in mice on a control fat diet and a high-fat diet (HFD) in vivo and in vitro. Heterozygous GIP-GFP KI mice (GIP-reduced mice [GIPgfp/+]) exhibited reduced GIP secretion; in the homozygous state (GIP-lacking mice [GIPgfp/gfp]), GIP secretion was undetectable. When fed standard chow, GIPgfp/+ and GIPgfp/gfp mice showed mild glucose intolerance with decreased insulin levels; bone volume was decreased in GIPgfp/gfp mice and preserved in GIPgfp/+ mice. Under an HFD, glucose levels during an oral glucose tolerance test were similar in wild-type, GIPgfp/+, and GIPgfp/gfp mice, while insulin secretion remained lower. GIPgfp/+ and GIPgfp/gfp mice showed reduced obesity and reduced insulin resistance, accompanied by higher fat oxidation and energy expenditure. GIP-reduced mice demonstrate that partial reduction of GIP does not extensively alter glucose tolerance, but it alleviates obesity and lessens the degree of insulin resistance under HFD conditions, suggesting a potential therapeutic value.